The Influence Of Store Image And Store Atmosphere On Customer Loyalty Mediated By Purchasing Decisions At Wizzmie Palu - Raehatuliana Raehatuliana; Elimawaty Rombe; Ponirin Ponirin; Hesti evrianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of store image and store atmosphere on customer loyalty, with purchasing decisions as a mediating variable. This research was conducted on Wizzmie customers in Palu City using a quantitative approach. Data were obtained from 120 respondents through questionnaires and analyzed using the Partial Least Squares (PLS) method. The results showed that store image has a significant influence on customer loyalty. Store image has a significant effect on purchasing decisions. Store atmosphere has a significant effect on customer loyalty. Store atmosphere has a significant effect on purchasing decisions. Purchasing decisions have a significant influence on customer loyalty. Store image mediated by purchasing decisions has a significant effect on customer loyalty. Store atmosphere mediated by purchasing decisions has a significant effect on customer loyalty.